HYGIENIC ASSESSMENT OF THE INFLUENCE OF ELECTRONIC CIGARETTES ON THE BLOOD PRESSURE IN MEDICAL STUDENTS’ ORGANISM - Derkach, Sergej; BlagaіaAnna (The Ukrainian Scientific Medical Youth Journal, 2020)
Blood pressure is one of the critical indicators of a person’s physiological state. This indicator and the pulse reflect the state of the cardiovascular system. Their values can directly or indirectly determine the presence of diseases of the heart and blood vessels, and other organs. Therefore, determination of blood pressure among people of different levels of health is an urgent task of modern medicine. The aim of the work: hygienic assessment and monitoring of blood pressure in medical students smoking e-cigarettes. Materials and methods: Quantitative and qualitative analysis of the level of systolic, diastolic pressure, mean arterial and pulse pressure in medical students aged 18-23 years, before and after smoking e-cigarettes was carried out. Results: The findings of the study fully reflect the importance of tonometry. Thus, the level of systolic blood pressure increased after 10 minutes by an average of 7.7%, but after 50 minutes returned to optimal value. The level of diastolic blood pressure increased after 10 minutes by an average of 8.8%, but after 50 minutes – an increase of 4%. Conclusions: This type of changes in the short period are not critical, as the body’ compensatory mechanisms stabilize hemodynamic parameters, but daily smoking can lead to the development of COPD, as well as pathology of the cardiovascular system, including myocardial ischemia or heart failure. Therefore, smoking e-cigarettes cannot be attributed to a harmless type of habit.